(untitled) (World Science, 2019)
Introduction: According to existing views, the ingrown nail is one of the diseases that often occurs in surgical practice and causes considerable suffering in patients and significantly restricts them in the performance of professional duties; reduces the physical activity and psychoemotional tone of the patient. Aim: Given that the number of patients with ingrown nail is steadily increasing, that today there are about 200 surgeries in the ingrown nail, and many of them do not take into account the etiological and pathogenetic components. The author’s team decided to research and review common methods of treatment of ingrown nails Materials and methods: A library fund was worked out regarding the problem of ingrown toenails. the workings out of clinics of Ukraine and other countries were worked out Results: Today, there are more than 150 methodological approaches to treating ingrown nail in the world. None of these procedures is Ideal for Achieving aesthetic results with low cost, recurrence and complication rates. Conclusions: The identified problems lead to the need to find a new less traumatic and economical method of treatment of ingrown nail, which will be characterized by rapid recovery of the patient and reduction of possible relapses.